Illness Narrative Master Plots Following Musculoskeletal Trauma and How They Change over Time, a Secondary Analysis of Data - Andrew Soundy; Maria Moffatt; Nga Man (Nicole) Yip; Nicola Heneghan; Alison Rushton; Deborah Falla; Lucy Silvester; Nicola Middlebrook (Behavioral Sciences)
Introduction; to the best of the authors knowledge, no past research has established how illness narrative master plots are expressed initially and then if and how they change longitudinally following musculoskeletal trauma. The aim of the present research was to consider how specific master plots were expressed, interact, and change across time following musculoskeletal trauma. Methods: A narrative analysis was undertaken that included individuals who had experienced a musculoskeletal traumatic injury. Individuals were included if they were an inpatient within 4 weeks of the first interview, had mental capacity to participate, and were able to communicate in English. Three interviews were undertaken (within 4 weeks of injury, then at 6- and 12-months post-injury). A 5-stage categorical form—type narrative analysis was performed. Results: Twelve individuals (49.9 ± 17.5 years; 7 male, 5 female) completed interviews at three time points following the trauma event (<4 weeks, 6 months, and 12 months). Three main narrative master plots appeared to work together to facilitate a positive accommodation of the trauma event into the individual’s life. These included the resumption narrative, the activity narrative, and the quest narrative. Finally, less often regressive narratives were identified, although these narratives were, at times, actively avoided. Discussion: The current results provide important consideration for how narratives are used within clinical practice, in particular the value of how these three narratives could be accessed and promoted.